Territorial dynamics and socio-environmental challenges in the contemporary Amazon: An introduction to the debate (Desenvolvimento em Questão, 2025)
This editorial analyzes the territorial configuration of the contemporary Amazon, marked by the persistence of an extractivist development model that generates deep socio-environmental contradictions. The analysis begins with the reconfiguration of space, demonstrating the formation of a heterogeneous and unequal urban network driven by distinct vectors of capital and state action, producing everything from regional metropolises to corporate cities and nodes of precarious services. It then explores the dichotomy between economic growth and social well-being, highlighting the persistence of high vulnerability rates in territories of great mineral wealth, where the precariousness of basic sanitation serves as a critical indicator of structural inequality. The study also addresses local responses to this reality, examining how the absence of the State has compelled the emergence of community-based environmental management strategies and how investment in basic infrastructure becomes a catalyst for sustainability. The editorial deepens the critique by dissecting the dominant agrarian matrix, identifying extensive cattle ranching and logistic expansion as drivers of deforestation and chemical intensification as a new frontier of environmental impact. In contrast, it analyzes the trajectories of sociobiodiversity, which face institutional and regulatory paradoxes that undermine their potential. Finally, the analysis turns to governance, arguing that national political polarization conceals an extractivist consensus that perpetuates a colonial logic, preventing the construction of a sustainable future for the region. The discussion culminates in a reflection on the 30th Conference of the Parties (COP 30), positioning it as a crucial moment that may either reinforce or challenge these historical dynamics.